USING PEDAGOGICAL TECHNOLOGIES IN WORKING WITH PARENTS OF PRESCHOOL CHILDREN WHEN TEACHING DRAWING SKILLS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
In the article, the author pays special attention to the importance of using pedagogical technologies in working with parents to preserve and develop parental relationships with preschool children.These technologies instill confidence in children, broaden their horizons, and technologies give the child the opportunity to cope with internal experiences and improve relationships with their parents.